What could infant and young child nutrition learn from sweatshops? - Sagoe-Moses Isabella; Ansett Sean; Singer Peter A (BMC, 2011)
Abstract Background Adequate infant and young child nutrition demands high rates of breastfeeding and good access to nutrient rich complementary foods, requiring public sector action to promote breastfeeding and home based complementary feeding, and private sector action to refrain from undermining breastfeeding and to provide affordable, nutrient rich complementary foods. Unfortunately, due to a lack of trust, the public and private sectors, from both the North and the South, do not work well together in achieving optimal infant and young child nutrition. Discussion As the current debate in infant and young child nutrition is reminiscent of the "sweatshop" debate fifteen years ago, we argue that lessons from the sweatshops debate regarding cooperation between public and private sectors - and specific organizational experiences such as the Ethical Trading Initiative in which companies, trade unions, and civil society organizations work together to enhance implementation of labour standards and address alleged allegations - could serve as a model for improving cooperation and trust between public, civil society and private groups, and ultimately health, in infant and young child nutrition. Summary Lessons from the sweatshops debate could serve as a model to promote cooperation and trust between public and private groups, such that they learn to work together towards their common goal of improving infant and young child nutrition.